Sosialisasi Tentang Gejala, Cara Penularan dan Pengobatan Tuberkulosis Paru Pada Pasien dan Keluarganya di Masa Pandemi Covid-19 - Elpira Asmin; Octovina Toressy (Jurnal Pengabdian Pada Masyarakat, 2022)
SOCIALIZATION ABOUT SYMPTOMS, MODES OF TRANSMISSION AND TREATMENT OF LUNG TUBERCULOSIS IN PATIENTS AND THEIR FAMILIES DURING THE COVİD-19 PANDEMIC. Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis (M.tb). Tuberculosis itself became one of the five main causes of disease burden in 2017 in Indonesia. The discovery of TB cases in Indonesia has declined sharply due to the COVID-19 pandemic. Data from the Ministry of Health in 2020 noted that there were only 271,750 TB cases that were notified or found, a sharp decline when compared to the findings in 2019 of 568,987 cases. The outbreak of the corona virus has caused most of the resources available in society to be devoted to dealing with the disease. As a result, the prevention of other diseases has been neglected, including pulmonary TB. At the Hutumuri Health Center Ambon, throughout 2020, 4 cases of pulmonary TB were found, and in 2021 there were 6 cases of pulmonary TB. In the last 2 years, the findings of new cases in the working area of ​​the Hutumuri Health Center did not meet the target set by the Maluku Provincial Health Office, namely 13 new cases for each public health center (PHC) each year. Community service activities were carried out for 3 days, on March 2 , 4 and 5, 2022 using counseling methods, distributing leaflets, as well as providing Information Education and Communication (IEC) to the general public and pulmonary TB sufferers which were carried out at the PHC and houses of Hutumuri villagers.